Qué actividades generan ingresos económicos para mejorar el bienestar de las familias - Espejo Lizarraga, Liliana Maribel (2019)
This Work of Professional Proficiency is called: activities to generate economic income to improve our family welfare looks for achieving learning within the course of Social Personnel and they are significant for students, being one task to contribute to the integral development of the student and society._x000D_ In this professional proficiency work, it describes in a first part the structuring of the learning session with the necessary components according to the scheme that is available, as well as the respective annexes, which are part of it, as a second part we find a scientific theoretical support in which the theoretical foundations are raised the same that support this section and finally a third part that deals with concerns a pedagogical support that guides the contributions of the didactics and the pedagogical orientations that are necessary for it._x000D_ For that reason, I leave this Work of Professional Proficiency to considerate, in compliance with the regulations of the University regulations in charge